Population Genomic Structure and Recent Evolution of Plasmodium knowlesi, Peninsular Malaysia - Hocking, Suzanne E.; Divis, Paul Cliff Simon; Kadir, Khamisah Abdul; Singh, Balbir; Conway, David J. (CDC Centers for Disease Control and Prevention, 2020)
Most malaria in Malaysia is caused by Plasmodium knowlesi parasites through zoonotic infection from macaque reservoir hosts. We obtained genome sequences from 28 clinical infections in Peninsular Malaysia to clarify the emerging parasite population structure and test for evidence of recent adaptation. The parasites all belonged to a major genetic population of P. knowlesi (cluster 3) with high genomewide divergence from populations occurring in Borneo (clusters 1 and 2). We also observed unexpected local genetic subdivision; most parasites belonged to 2 subpopulations sharing a high level of diversity except at particular genomic regions, the largest being a region of chromosome 12, which showed evidence of recent directional selection. Surprisingly, we observed a third subpopulation comprising P. knowlesi infections that were almost identical to each other throughout much of the genome, indicating separately maintained transmission and recent genetic isolation. Each subpopulation could evolve and present a broader health challenge in Asia.